Estimating the reliability of the inspection system employed for detecting defects in rail track using ultrasonic guided waves - Khalil, Abdelgalil (2022)
This work focuses on the implementation of a data-based method to determine the inspection system reliability in terms of detecting different types of damages in rail track specimens using ultrasonic guided Rayleigh waves and a probability of detection (POD) technique. In this study, the reliability is tested against a surface crack (SC) and a sub-surface damage – a through side thickness hole (TSTH). The guided Rayleigh waves are generated using a custom-designed sensor that explicitly excited ultrasonic Rayleigh surface waves in the specimen and the propagating waves are sensed on the rail track surface. The wedge shape design of the sensor helps to excite a specific ultrasonic mode in the sample thereby hindering the ultrasonic energy of other coupled guided waves that can propagate simultaneously and the angle of the wedge is determined according to the Snell’s law relying on the wave velocity of Rayleigh wave and bulk longitudinal wave. The guided wave responses as a function of varying severity of defects are obtained through a simulation study after the verification of the obtained guided wave responses with the help of an experimental study. A damage index (DI) is defined depending on defect size that gives the trend of rising damage severity from the captured ultrasonic responses and for monitoring defects in the rail track specimens. This DI is eventually fed into the POD model to determine the probability of defect detection which in turn helps to determine the inspection system reliability. The POD method also helps to study the critical design parameters that could affect or improve the crack detection results.